Lipid Nanoparticles for Brain Tumor Theranostics: Challenges and Status - Kaur N.; Gautam P.; Nanda D.; Meena A.S.; Shanavas A.; Prasad R. (My University, 2025)
Lipid nanoparticles have been recognized as a powerful weapon for delivering various imaging and therapeutic agents to the localized solid tumors, especially brain tumors individually or in combination. Promisingly, lipid-based nanosystems have been considered as safe delivery systems which are even approved by the Food and Drug Administration (FDA) and the European Medicines Agency (EMA). One recent spotlight of lipid nanoparticles as COVID-19 mRNA vaccines where lipid nanoparticles play an important role in effectively protecting and delivering mRNA to the desired cells. As of now, successive progress in lipid-based nanocarriers, viz., nanoliposomes, solid lipid nanoparticles, ionizable lipid nanostructures, etc., with better biochemical and biophysical stabilities, has been noticed and reported. Moreover, lipid nanostructures have been considered as versatile therapeutics platforms for a variety of diseases due to their biocompatibility, ability to protect and deliver therapeutics to the localized site, and better reproducibility and reliability. However, lipid nanoparticles still face morphological and biochemical changes upon their in vivo administration. These changes alter the specific biological and pathological response of lipid nanoparticles during their personalized brain tumor theranostics. Second, lipid nanomedicine still faces major challenges of zero premature leakage of loaded cargo, long-term colloidal stability, and off targeting. Herein, various lipid-based nanomedicines for brain tumor imaging and therapeutics “theranostics” have been reviewed and summarized considering major aspects of preclinical and clinical studies. On the other hand, engineering and biological challenges of lipid theranostics systems with relevant advantages and guidelines for clinical practice for different brain tumors have also been discussed. This review provides in-depth knowledge of lipid nanoparticle-based theranostics agents for brain tumor imaging and therapeutics. © 2024 American Chemical Society.